Comparative study: Indonesian and Indian government policies in managing the problem of dual citizenship - Yulianto Syahyu (International Journal Labs, 2025)
The Indonesian diaspora continues to fight for the right to dual citizenship in various countries around the world. The research aims to explore the concepts of limited dual citizenship and the concept of dual citizenship within the context of India with a study of cross-country analysis of Indonesia and India. The study employs normative legal research to analyze dual citizenship policies in these two countries, focusing on the relevant laws and regulations of each country. Furthermore, it utilizes descriptive comparative analysis to provide a comprehensive and systematic comparison of dual citizenry policies between the two countries. The results show that the Indonesian government's policy on the demand for dual citizenship is different in both countries. In addition, there are differences and similarities in the approaches taken by both countries, especially in the Overseas Citizenship of India (OCI) policy and the dual citizenship policy. This research could provide valuable insights for Indonesia in crafting similar policies that facilitate easier access and engagement for its diasa.